HOW CAN CLASSROOM ACTIVITIES BOOST STUDENT'S IDEA GENERATION FOR WRITING - Raxmatullina Rozaliya Xafizovna; Alimova Dildora Komiljon kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Many students struggle to generate ideas during writing lessons, which can limit their creativity and reduce the quality of their work. This article shows how engaging classroom activities can spark students’ thinking and help them produce more ideas for writing. Methods include brainstorming, clustering, guided exercises, as well as interactive approaches such as reading books by roles, acting out scenes, and drawing inspiration from stories like Harry Potter. These activities not only help students develop their ideas but also make writing enjoyable, boosting their confidence and creativity as young writers.